Community Water Fluoridation: Caveats to Implement Justice in Public Oral Health - Song, Youngha (Int J Environ Res Public Health, 2021)
Community water fluoridation (CWF), a long-established public health intervention, has been studied for scientific evidence from both of yea and nay standpoints. To justify CWF with scientific evidence inevitably leads to ethical justification, which raises the question of whether oral health is of individual concern or social responsibility. As dental caries is a public health problem, public health ethics should be applied to the topic instead of generic clinical ethics. From both pro- and anti-fluoridationists’ perspectives, CWF is a public health policy requiring a significant level of intervention. Thus, there needs to take further considerations for justifying CWF beyond the simple aspect of utility. For further ethical considerations on CWF, three caveats were suggested: procedural justice, social contexts, and maintenance of trust. The process to justify CWF should also be justified, not simply by majority rule but participatory decision-making with transparency and pluralistic democracy. Social contexts are to be part of the process of resolving conflicting values in public health interventions. Public trust in the dental profession and the oral healthcare system should be maintained over the considerations. This article suggests accountability for reasonableness as a framework to consider infringement by CWF for public justification of its implementation.